Trade Facilitation Indicators The Impact on Trade Costs - Moïsé, Evdokia (OECD Trade Policy Papers, 2011)
This report presents the findings of the OECD indicators for assessing the economic and trade impact of specific trade facilitation measures in OECD countries. Twelve trade facilitation indicators (TFIs) have been constructed, corresponding to the main policy areas under negotiation at the WTO, with the aim to estimate the impact of addressing specific facilitation hurdles in the trade procedures of a given country. For OECD countries, the policy areas that seem to have the greatest impact on trade volumes and trade costs are advance rulings, information availability, formalities and procedures and inter-agency cooperation. If all TFIs are added their cost reduction potential would reach almost 10% of trade costs, which is an estimate consistent with existing literature. The use of individual trade facilitation indicators should enable countries to better assess which trade facilitation dimensions deserve priority. The OECD TFI project is now expanded to cover countries outside the OECD area